Increasing girls’ physical activity during an organised youth sport basketball program: a randomised controlled trial protocol - Guagliano, Justin M.; Lonsdale, Chris; Kolt, Gregory S.; Rosenkranz, Richard R. (My University, 2014)
Background: Participation in organised youth sports (OYS) has been recommended as an opportunity to increase young peoples’ moderate-to-vigorous physical activity (MVPA) levels. Participants, however, spend a considerable proportion of time during OYS inactive. The purpose of this study, therefore, was to investigate whether coaches who attended coach education sessions (where education on increasing MVPA and decreasing inactivity during training was delivered) can increase players’ MVPA during training sessions over a 5-day basketball program compared to coaches who did not receive coach education sessions. Methods/design: A convenience sample of 80 female players and 8 coaches were recruited into the UWS School Holiday Basketball Program in Greater Western Sydney, Australia. A two-arm, parallel-group randomised controlled trial was employed to investigate whether coaches who attended 2 coach education sessions (compared with a no-treatment control) can increase their players’ MVPA during training sessions over a 5-day basketball program. Objectively measured physical activity, directly observed lesson context and leader behaviour, player motivation, players’ perceived autonomy support, and coaching information (regarding training session planning, estimations on player physical activity and lesson context during training, perceived ability to modify training sessions, perceived importance of physical activity during training, intention to increase physical activity/reduce inactivity, and likelihood of increasing physical activity/reducing inactivity) were assessed at baseline (day 1) and at follow-up (day 5). Linear mixed models will be used to analyse between arm differences in changes from baseline to follow-up on all outcomes. Discussion: The current trial protocol describes, to our knowledge, the first trial conducted in an OYS context to investigate the efficacy of an intervention, relative to a control, in increasing MVPA. This study’s findings will provide evidence to inform strategies targeting coaches to increase MVPA in OYS, which could have major public health implications, given the high proportion of children and adolescents who participate in OYS globally.
Keywords: Moderate-to-vigorous physical activity; Inactivity; Youth sport; Organized sport; Training; Coach; Children; Adolescents; Coach education